Degradação bacteriana da MOD excretada por Microcystis aeruginosa (Cyanobacteria) em culturas, fracionada e submetida à radiação UV - Moreira, Ingritt Caroline (Universidade Federal de São Carlos, 2009)
Solar radiation can change DOM in aquatic environments making compounds more labile or recalcitrant to biodegradation. Thus, solar radiation, especially UV, indirectly interfere in the microbial community in order to increase or decrease their growth. The objective was to verify the interference of UV-A + B on the bioavailability of DOM separated into different fractions (molecular weight), from release of cells in stationary phase of M. aeruginosa. DOM released from cyanobacteria was separated by tangential ultra-filtration and these were inoculated bacterial community of Barra Bonita reservoir. Bacterial community dynamic was monitored by measures of density and biomass and bacterial consumption of carbon from DOM by measures of DOC. Frequency of bacterial morphotypes were also calculated. All three fractions of DOM investigated were highly available to the bacterial community. The fraction of cultures with DOM<3 kDa and DOM>30 kDa demonstrated to be more vulnerable to UV radiation, corroborated by many statistical differences found for bacterial density during 27 days of incubation. At 15 days of incubation, the cultures with irradiated DOM>30 kDa showed a second peak in bacterial density and biomass that can be understood as an event of succession in bacterial community. Changes in relative frequency of bacterial morphotypes over incubation period suggest an episode of succession during the different stages of degradation of DOM. It was suggested that the majority of DOC released from a bloom of cyanobacteria is rapidly mineralized. Furthermore, the constant blooms, or ever high biomass of M. aeruginosa during the year, mean that such bacterial consortia are always available.
Keywords: Ecologia aquática; Matéria orgânica dissolvida; Radiação ultravioleta; Microcystis aeruginosa; Bactérias; Degradação; CIENCIAS BIOLOGICAS::ECOLOGIA